Study on the method and model of water balance allocation of the Yellow River with overall fairness and efficiency - Yu Wang; Shaoming Peng; Jian Wu; Fang Wan; Xiaokang Zheng; Xiangnan Zhou; Wenxiu Shang; Fei Zhang (Water Supply, 2023)
Under the changing environment, the problems of the water cycle and water resources in the basin become extremely complex, and the coordination of water use efficiency and fairness is extremely difficult. This paper takes the Yellow River Basin as the key research area and creates a balanced allocation method and model of water resources that take into account the fairness and efficiency of water use. The dynamic equilibrium allocation of water resources increment brought by new water source projects and regulation projects is realized, and the fine-tuning optimization of the water distribution scheme is realized. The results show that the optimal adjustment strategy of the water diversion scheme is to increase the upstream water allocation, and the adjustment range is 2.13%. The water allocation in the middle reaches was slightly increased by 0.25% to reduce the downstream and Hebei Province, Tianjin water allocation, and the adjustment range is −3.81%. The optimization scheme reflects the principle of ecological priority, guarantees the basic ecological environment water use in the Yellow River, balances the fairness and efficiency of economic and social water use outside the river, and provides technical support for water resources security in water-shortage basins. HIGHLIGHTS The method and model of incremental dynamic equilibrium allocation of water resources in the Yellow River Basin were proposed in this study. The scenario analysis was carried out to study the strategies of water diversion schemes such as optimizing the direction and amplitude of adjustment, so as to improve the adaptability of the water distribution scheme to the changing environment.; From the perspective of fairness, the distribution of rigid water demand such as domestic and industrial water demand in each province of the basin is given priority, and then the efficiency factors of rigid elasticity and elastic water demand distribution in each province are considered.;